APPLICATION OF USER-CENTERED DESIGN (UCD) METHOD IN THE IMPLEMENTATION OF CUSTOMER RELATIONSHIP MANAGEMENT INFORMATION SYSTEM AT SALON D’MUTIA MUARA ENIM-BASED SMS GATEWAY - Al Barroh , Aisyah (Journal of Information Systems Management and Digital Business, 2023)
Salon D'Mutia Muara Enim is a company engaged in services, spa, beauty and personal care that has customers ranging from various characters and levels. This study uses the User Centered Design (UCD) method as an effort to get new customers, increase relationships and maintain customer loyalty by placing customers as the center of the system development process. This research was developed using the Framework for the Application of System Thinking (FAST) method. The final result of this study is a website equipped with an SMS Gateway application.